Empowering Women in Irrigation Management : The Sierra in Peru - World Bank (Washington, DC, 2014)
This report tells the story of a gender pilot that was carried out in water users' organizations for irrigated agriculture in the Peruvian highlands or Sierra region. It was designed upon the request of Peru's ministry of agriculture, with the objective to strengthen the role of women in water management and to improve their condition as agricultural producers. At first, a gender diagnostic was carried out to better understand the different barriers that hinder the attendance and thus equality of participation of women in trainings and meetings. After this diagnostic, a discussion followed about the importance for a community of including women in water management. In response to these diagnostics and subsequent discussions, the water users resolved to set specific targets for becoming more inclusive organizations, and shaped the content and timing of their activities to allow a greater number of women to participate. The pilot, carried out between 2007 and 2009, improved women s technical skills, self-esteem and position in the water users organizations, and has raised awareness among the community members about women's specific needs and expectations related to water management for irrigated agriculture. The participatory methodology used in this pilot was designed with the support of the World Bank group gender action plan, and is currently being scaled up in the World Bank financed Sierra Irrigation Subsector Project (PSI Sierra).